Exploring the binding affinity of rutin, catechin, and epicatechin to ALK and caspase-3: implications for colorectal cancer treatment - Adhyaksa, I Nyoman Mahesa Praba; Pramesti, Ni Luh Putu Cintya; Susanti, Ni Made Pitri; Laksmiani, Ni Putu Linda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2022)
This study explores the interaction of rutin, catechins, and epicatechins with anaplastic lymphoma kinase (ALK) and caspase-3, focusing on their potential role in modulating the apoptotic mechanisms in colorectal cancer cells. The experimental approach included the preparation of ALK (PDB ID: 5USQ) and caspase-3 (PDB ID: 2XZT), validation of the docking process, optimization of the test compounds, and docking analyses. The molecular docking methodology was validated with an RMSD value of ≤ 3 Å. The docking outcomes revealed that rutin, catechins, and epicatechin exhibited lower binding affinity to ALK, with binding energies of -8.58 kcal/mol, -8.41 kcal/mol, and -7.82 kcal/mol, respectively, compared to ALK's native ligand (-10.27 kcal/mol). Conversely, these compounds demonstrated higher affinity to caspase-3 than its native ligand (-2.54 kcal/mol), with binding energies of -6.03 kcal/mol for rutin, -5.28 kcal/mol for catechins, and -4.95 kcal/mol for epicatechin. These findings suggest that rutin, catechins, and epicatechins hold promise as colorectal anticancer agents by potentially modulating the activity of ALK and caspase-3 through inhibition and activation mechanisms, respectively.